A Review of Running Mechanics in Obese or Overweight Individuals - Ebrahim Piri; Amir Ali Jafarnezhadgero (Biyumikānīk-i varzishī, 2023)
Objective Obesity and overweight have become global problems that can affect the mechanics of running in affected individuals. Therefore, the aim of the present study was to review the mechanics of running in obese or overweight individuals. Methods The present study was a library and systematic review. The search for articles in Persian and English was performed from the beginning of 2003 until the beginning of January 2023. This search was conducted in various databases, including WOS, SID, Magiran, Scopus, PubMed, ISC, and Google Scholar. Additionally, the type of selected studies included original research, review articles, and clinical trials. Seventeen related articles were selected based on inclusion and exclusion criteria. Finally, 12 articles related to running mechanics in overweight or obese individuals were analyzed. Results The review of three articles showed that there is a direct relationship between an increase in body mass index (BMI) and an increase in plantar pressure. Additionally, the results of two articles were related to the increase in loading rate in obese individuals while running. The findings of two articles indicated the collapse of the arches of the feet and ultimately the reduction of shocks caused by running. Examining the results of one of the articles showed that in overweight or obese individuals, doing exercises such as running can be a reason for micro fractures of the tibia. The findings of one of the articles also showed that people with a high body mass index have a lower range of motion than people with a normal weight while running. Finally, the findings of three articles in the field of muscle electrical activity showed that in overweight individuals, activities such as running can be effective in reducing the strength of plantar flexor muscles. Conclusion It seems that obese and overweight individuals are at risk of injury during running due to biomechanical reasons.